AUTOMATED METHOD OF SOLVING THE TWO-DIMENSIONAL INVERSE PROBLEM OF ELECTROMAGNETIC INDUCTION WITHIN THE EARTH - Zhdanov M.S.; Chernyak V.V. (My University, 1987)
The basic problem of modern geolectric science is the development of methods for interpreting the data of electromagnetic investigations in areas with complex laterally nonuniform structure of the geoelectric section. A promising approach to the interpretation of electromagnetic data is that based on linearization of the inverse problem. This paper presents an algorithm for solving the inverse problem over two-dimensionally nonuniform sections in which it is reduced to the following procedures: (a) determination of the lateral distribution of excess currents flowing in the inhomogeneity by solving the corresponding linear integral Fredholm equation; (b) determination of the electric field in the vicinity of the inhomogeneity by quadratures from the distribution of excess currents; (c) calculation of the excess conductivity from the electric field and excess current by Ohm's law.